Complexos à base de ligantes do tipo oxamato: estratégia metalossupramolecular no desenvolvimento de materiais moleculares e híbridos contendo nanotubos de carbono de poucas paredes - Walace Doti do Pim (2016)
In this work the heterobimetallic compounds containing the ligand edpba4 [H4edpba = N,N-2,2-ethylenediphenylenebis(oxamic acid)] are described. The compound [Mn5Cu5(edpba)5(dmso)7(H2O)5]·2dmso·H2O was obtained as a single crystal, allowing to solve its structure by X-ray diffraction. The magnetic properties of this system were investigated, which showed an antiferromagnetic coupling between the metal centers with J = 28,1(2) cm1 leading to a ferrimagnetic system with total spin in the fundamental state equal to 10. Compound [Co6Cu6(edpba)6(H2O)17]·33H2O also had its structure elucidated by X-ray diffraction. The magnetic properties of this system were investigated, but the construction of a theoretical model to fit the experimental data of this compound was not possible yet. The investigation of systems containing the ligand H2edpba2 and the precursors [Ni(bipy)]2+ and [Cu(bipy)]2+ [bipy = 2,2-bipyridine] are also described. Three compounds were formed. The mononuclear system [Ni(H2edpba)(bipy)]·dmso had its structure solved by X-ray diffraction. From this NiII mononuclear compound and CuCl2 was prepared the coordination polymer {[Cu(H2edpba)(bipy)]·3H2O·dmso}n. This compound was obtained as few single crystals together with a polycrystalline solid. From the precursor [Cu(bipy)]2+, it was formed the similar coordination polymer {[Cu(H2edpba)(bipy)]·1,5H2O}n. The three compounds had their crystal structures solved by X-ray diffraction. Besides, the magnetic properties of the coordination polymer {[Cu(H2edpba)(bipy)]·1,5H2O}n show a weak antiferromagnetic coupling between the CuII ions (J = 0,40 cm1). It was prepared the precursor (bmim)2[Cu(opba)]3H2O [bmim = 1-butyl-3-methylimidazolium and H4opba = ortho-phenylenebis(oxamic acid) , which was planned to interact with few-walled carbon nanotubes to develop composites containing the coordination polymer [MnCu(opba)]n. The studies using Raman spectroscopy showed that the coordination polymer interacts with the metallic nanotubes independently of the tubes diameter, and there is a selective interaction of this polymer with semiconductor nanotubes with diameter higher than ca. 1.47 nm. Transmission electron microscopy images and Raman spectroscopy studies showed that the coordination polymer probably involves the nanotubes forming a spiral. Using the same precursor, (bmim)2[Cu(opba)]3H2O, it was prepared the 2D-ferrimagnetic heterobimetallic compound, (bmim)2Mn2[Cu(opba)]311H2Odmso. This compound was characterized by magnetization measurements versus temperature in different values of applied magnetic fields, which revealed the presence of a metamagnetic behavior due to the weak antiferromagnetic interactions between the planes. Composites were prepared with 1, 5 and 10% of few-walled carbon nanotubes in the matrix of the 2D heterobimetallic compound. The in situ insertion of carbon nanotubes in the matrix of the compound was proved by transmission electron microscopy images, and the complex-tube interactions were investigated by Raman spectroscopy. Magnetic studies showed that the insertion of the tubes in the matrix of the compound did not modify the magnetic properties of the molecule-based magnet.